Baseline Lymphopenia: A Predictor Of Poor Outcomes In HER2 positive Metastatic Breast Cancer Treated With Trastuzumab - Che YQ; Zhang Y; Wang D; Liu HY; Shen D; Luo Y (Dove Medical Press, 2019)
Yi-Qun Che,1 Yue Zhang,1 Di Wang,1 Hui-Ying Liu,2 Di Shen,1 Yang Luo3 1Department of Clinical Laboratory, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100021, People’s Republic of China; 2Department of Clinical Laboratory, Beijing Chaoyang District Sanhuan Cancer Hospital, Beijing 100122, People’s Republic of China; 3Department of Medical Oncology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100021, People’s Republic of ChinaCorrespondence: Yang LuoDepartment of Medical Oncology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 17 Panjiayuan Nanli, Chaoyang District, Beijing 100021, People’s Republic of ChinaTel + 86-10-87788820Fax + 86-10-87788820Email dryangluo@163.comPurpose: Despite selection based on human epidermal growth factor receptor 2 (HER2) overexpression, not all HER2-positive patients benefit from trastuzumab therapy. Recent reports indicate that trastuzumab treatment failure may be associated with immune system dysfunction. We examined the prognostic relevance of the absolute lymphocyte count (ALC) in patients with HER2-positive metastatic breast cancer (MBC) who received trastuzumab combined with chemotherapy.Methods: Baseline ALC and neutrophil-to-lymphocyte ratio (NLR) data from trastuzumab-treated patients with MBC were studied retrospectively, and associations between baseline ALC and clinical characteristics evaluated. Kaplan–Meier analysis and the Cox regression hazard model were applied to assess effects on outcomes.Results: Of a total of 68 patients, 19.1% (13/68) had baseline ALCs ≤ 1 G/L. Baseline lymphopenia was correlated with increased lactate dehydrogenase (LDH) and higher NLR. In univariate analysis, higher alkaline phosphatase (ALP) was associated with inferior overall survival (OS) (P = 0.001); higher LDH was associated with inferior progression-free survival (PFS) (P = 0.045) and OS (P = 0.010). We did not observe any differences in objective response rate or disease control rate between patients with lymphopenia and those with normal ALC. Importantly, patients with baseline lymphopenia had inferior PFS (0.60 years vs 1.17 years, P = 0.000009) and OS (1.88 years vs 3.80 years, P = 0.0003). In multivariable analysis, significance of ALCs was retained for lymphopenia (PFS: P = 0.0005; OS: P = 0.016).Conclusion: Our data indicate that baseline ALC value of ≤1 G/L is a predictor of poor outcomes, but not of response, in patients with MBC treated with trastuzumab.Keywords: absolute lymphocyte count, metastatic breast cancer, overall survival, progression-free survival